Bioactive Composition and Nutritional Profile of Microgreens Cultivated in Thailand - Laddawan Kowitcharoen; Surisa Phornvillay; Pornpan Lekkham; Nutthachai Pongprasert; Varit Srilaong (Applied Sciences, 2021)
Microgreens are young and tender leafy vegetables that have gained wider consumer acceptance. This is attributed to their low caloric composition and rich micronutrient and antioxidant composition. The present study investigated the bioactive composition and proximate analysis of fourteen microgreens belonging to Brassicaceae, Fabaceae, Pedaliaceae, Polygonaceae, Convolvulaceae, and Malvaceae. All the microgreens showed low calories (20.22 to 53.43 kcal 100 g−1) and fat (0.15 to 0.66 g 100 g−1), whilst mung bean and lentil microgreens showed considerable amounts of carbohydrate (7.16 g 100 g−1) and protein (6.47 g 100 g−1), respectively. Lentil microgreens had the highest total chlorophyll (112.62 mg 100 g−1) and carotenoid (28.37 mg 100 g−1) contents, whilst buckwheat microgreens showed the highest total phenolic content (268.99 mg GAE 100 g−1) and DPPH• scavenging activity (90.83 mM TEAC g−1). The lentil microgreens also presented high ascorbic acid content (128.70 mg 100 g−1) along with broccoli, Chinese kale, purple radish, and red cabbage microgreens (79.11, 81.33, 82.58, and 89.49 mg 100 g−1, respectively). Anthocyanin content was only detected in purple radish (0.148 mg CGE 100 g−1) and red cabbage (0.246 mg CGE 100 g−1). The results provide basic information and highlight the benefits of utilizing genetic biodiversity to obtain microgreens with the desired nutrients and antioxidants.